Sentinel Node Biopsy in Young Patients with Atypical Melanocytic Tumors of the Head and Neck. Issue 2 (May 2019) - Pfau, David; Tamaki, Akina; Hoppe, Kathryn R.; Honda, Kord; Rezaee, Rod; Zender, Chad A.
Objective: To examine the diagnostic value of the sentinel lymph node biopsy in pediatric through young adult head and neck melanocytic tumors of unknown malignant potential. Study Design: Retrospective case series. Setting: Single academic institution. Subjects and Methods: Demographics, histology, and outcomes were examined in 14 patients aged 4 to 24 years with head and neck melanocytic tumors of unknown malignant potential. Information on age at diagnosis, primary lesion characteristics, and sentinel lymph node biopsy were compared. Results: Of 14 patients meeting criteria for head and neck melanocytic tumors of unknown malignant potential, 8 patients underwent sentinel lymph node biopsy (57%). Of those, 4 biopsies (50%) had positive sentinel nodes. All patients undergoing sentinel lymph node biopsy had primary lesions greater than 1 mm depth or mitotic rate of at least 1 mitosis per mm 2 . No patients had recurrence of their primary lesion at time of follow-up. Conclusion: Our data show a high rate of node-positive sentinel lymph node biopsy for pediatric and young adult head and neck patients with melanocytic tumors of unknown malignant potential, supporting the value of sentinel lymph node biopsy in this population.